The Adsorption of Perfluorooctane Sulfonate onto Sand, Clay, and Iron Oxide Surfaces - Johnson, Ramona L; Anschutz, Amy J; Smolen, Jean M; Simcik, Matt F; Penn, R. Lee (Journal of chemical and engineering data, 2007)
Fluorinated anionic surfactants have drawn considerable attention due to recent work showing significant concentrations in surface waters and biota from around the globe. A detailed understanding of the transport and fate of fluorinated surfactants through soil and like media must include an elucidation of mineral surface chemistry. Five materials were equilibrated with solutions of perfluorooctane sulfonate (PFOS) to characterize adsorption:  kaolinite, Ottawa sand standard, synthetic goethite, Lake Michigan sediment, and iron-coated sand from Mappsville, VA. Aqueous and adsorbed PFOS was quantified with LC/MS (mass balance average:  101 ± 12 %, n = 37). The materials showed a near linear increase in adsorption as the equilibrium concentrations increased. Isotherms and calculated solid/solution distribution ratio experiments indicated that PFOS adsorption is significant but smaller than hydrocarbon analogues or organic compounds of similar molecular weight. Surface area normalized adsorption increased for the materials in the following order:  goethite < kaolinite < high iron sand < Ottawa sand standard. Experimental results and comparisons to published data suggest that organic carbon may play an important role in sorption whereas electrostatic attraction may play a role when organic carbon is not present.